ChemInform Abstract: Template‐Dependent Photochemical Reactivity of Molecular Metal Oxides. Issue 34 (August 2015) - Tucher, Johannes; Peuntinger, Katrin; Margraf, Johannes T.; Clark, Timothy; Guldi, Dirk M.; Streb, Carsten
Abstract Single crystals of Bu4N [(Bi(dmso)3)2V12O33X] ·xDMSO (X: Cl (I), Br (II)) are prepared by dissolving (Bu4N)3[H3V10O28], Bi(NO3)2, and NaX in aqueous DMSO at 80 °C followed by addition of Bu4NOH (80 °C, 1 h, 67 and 71% yield, resp.).